Development of Plant Diversity Media and Plant Determination Key in Learning Plantae with the SETS Approach in High School X Grade - Fahuwa, Istafta Dina; Rahayu, Enni Suwarsi (FMIPA UNNES, 2021)
The results of interviews with biology teachers at SMA N 1 Bangsri showed that 69.4% of X MIPA students received incomplete scores on the Plantae material. This is because the media is not used that can guide students in classifying the plants in the school environment according to the expected competencies. This study aims to identify the diversity of plants in SMA Bangsri. This research aims to identify the diversity of plants found in SMA Bangsri and to analyze the validity and practicality of the plant diversity media and plant determination key as a classification guide, which will be used in the SETS approach of Plantae learning. This research, which was implemented at SMA N 1 Bangsri, used the Research and Development method with the following steps: identification of potentials and problems, data collection, product design, product validation, product revision, and small-scale trials. Small-scale trials of plant diversity media and the plant determination key were carried out on 36 students of XI MIPA 5 using a practicality questionnaire. The results of this study indicate that the plants diversity in SMAN 1 Bangsri includes 92 types of plants consisting of 6 divisions namely Bryophyta, Pteridophyta, Coniferophyta, Cycadophyta, Gnetophyta, and Magnoliophyta. Validity of the plant diversity media and the plant determination key according to the material validator is 91.67%, the media validator is 96.67% with ‘very valid’ criteria. While the media practicality assessment by 69.4% of students stated that the media was ‘very practical’ and 30.6% of students stated that the media was ‘practical’, and teacher assessing the media 93.75% with very practical criteria.This shows that the plant diversity media and the plant determination key are very valid and practical for students to use in the Plantae learning using the SETS approach in X grade.